The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1001/jamanetworkopen.2022.52209
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Breast Cancer Risks Among Women Receiving Mammograph Screening

Abstract: ImportanceBreast density is an independent risk factor for breast cancer. Despite the proliferation of mandated written notifications about breast density following mammography, there is little understanding of how women perceive the relative breast cancer risk associated with breast density.ObjectiveTo assess women’s perception of breast density compared with other breast cancer risks and explore their understanding of risk reduction.Design, Setting, and ParticipantsThis mixed-methods qualitative study used t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 59 publications
1
8
0
Order By: Relevance
“…Family history of breast cancer accounted for a small proportion of advanced breast cancers in premenopausal (8%) and postmenopausal women (5%) in our study. Studies have shown that women perceive family history of breast cancer as the primary breast cancer risk factor, with overweight/obesity and breast density less likely to be identified as primary risk factors for breast cancer . Patients need to be educated on factors that contribute most to development of advanced breast cancer (eg, having overweight/obesity and high breast density) and on primary prevention interventions that can modify these risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…Family history of breast cancer accounted for a small proportion of advanced breast cancers in premenopausal (8%) and postmenopausal women (5%) in our study. Studies have shown that women perceive family history of breast cancer as the primary breast cancer risk factor, with overweight/obesity and breast density less likely to be identified as primary risk factors for breast cancer . Patients need to be educated on factors that contribute most to development of advanced breast cancer (eg, having overweight/obesity and high breast density) and on primary prevention interventions that can modify these risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…Findings, similar to previously mentioned work [ 24 ], highlight that a multi-pronged approach to communication is likely to be needed to reach women of all ages, socioeconomic status, and health and media literacy levels. However, it is known that knowledge of breast cancer risk factors or intention to modify behavioural factors does not guarantee actual lifestyle change, that there has generally been a lack of awareness among women of lifestyle behaviour change as a form of breast cancer prevention [ 6 ], and women do not feel confident about actions they can take to mitigate breast cancer risk [ 29 ]. Therefore, well developed and accessible interventions are needed to facilitate this.…”
Section: Discussionmentioning
confidence: 99%
“…BC is a multi‐factorial disease (Hao et al., 2021), and family history is an important and unmodifiable risk factor (Beidler et al., 2023). Female FDRs, including mothers, sisters, and daughters of BC patients, have a 1.5‐ to 3‐fold greater risk of developing BC during their lifetime than the general population (Braithwaite et al., 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Mammography, clinical breast examination (CBE), and breast self-examination (BSE) are considered to be effective strategies for the early detection of BC (Zhou et al, 2014). In response to the rising incidence of BC, many countries have implemented national BC screening programs, such as the USA, Australia (Australian Government, 2020), most of the European Union countries , and China BC is a multi-factorial disease (Hao et al, 2021), and family history is an important and unmodifiable risk factor (Beidler et al, 2023). Female FDRs, including mothers, sisters, and daughters of BC patients, have a 1.5-to 3-fold greater risk of developing BC during their lifetime than the general population (Braithwaite et al, 2018).…”
Section: Introductionmentioning
confidence: 99%